Glucose levels in first 3 days and neurodevelopmental outcome at 1 year in low birth weight infants: A cohort study - Chandrasekaran, Ashok; Rao, P N Suman; Raman, Vijaya; Nesargi, Saudamini; Shekharappa, Chandrakala Bada; Sahoo, Jagdish Prasad; Ranjit, Thomas; Chico, Marie Shalini; Bhat, Swarnarekha (Indian Journal of Child Health, 2016)
Background: Definition of neonatal hypoglycemia is still controversial. Objective: To find the effect of blood glucose (BG) levels in the first 3 days of life, on developmental outcome at 1 year in low birth weight neonates